A methods study on Maple Leaf Enterprises - Butac, Aleczar Monis (College of Engineering, 2001)
Maple Leaf manufactures a basic consumer product-bags; therefore, demand for their product is sustainable. Maple Leaf's factory is located within the same street and subdivision as the owner's residence, which allows for close supervision and management accessibility to the workers. Also, workers are provided with sleeping quarters within the factory premises, hence, labor is available when necessary, especially during the peak months of production period. As in most single proprietorship entities, control and decision making within the company is centralized. It is evident that the company lacks delegation of responsibilities since the owner herself acts both as production and finance manager. Based on a series of ocular inspections of the factory, the group observed that the plant lay-out is quite limited, and that the production process needs improvement due to limited space, equipment on workers are positioned at random, and not according to an organized flow of the various production processes. The company still has much space to develop a more efficient system for quality control of its products. Analysis of the company's systems using Problem Analysis techniques shows improvement for their workflow when same activities are grouped together. A temporary storage area is placed near the sewing, cutting, and detailing area to minimize the production time. Problems on the working conditions are solved by putting up more windows, exhaust and electric fans. Workers attitude, on the other hand, can be improved by adding incentives and benefits and creating a more conducive environment. The company lacks standards to base its operations on. Analysis of the company's existing system shows that the company needed to reorganize its system. The problems the company is experiencing now is due to its lack of a standard system. From the analysis made, the group came up with a new system where the workers are required to sign a written agreement and be paid in full. There will be written and specified job descriptions to prevent doing the same work twice. The company will produce its own product to have a profit when there are no job orders. Implementation of the new system will minimize its problem and will improve productivity. Overall recommendations sums up for the company to reorganize their systems and procedures. Focusing on management procedures which include strict implementation of job descriptions, to avoid wage payment problems. Implementations of these alternatives should be done by the management as soon as possible. A complete reorganization of the company is what seems to be the best way for improving its work methods. Implementations and guidelines are then presented in the paper by the group for company improvement analysis.